Pengaruh Inisiasi Menyusu Dini terhadap Waktu Pengeluaran dan Perubahan Warna Mekonium Serta Kejadian Ikterik Fisiologis - Nicko Pisceski Kusika Saputra; Putri Sri Lasmini (Fakultas Kedokteran Universitas Riau, 2015)
One of the government’s efforts through the Millennium Development Goals (MDGs) in 2010 in reducing the infantmortality rate in Indonesia is improving infants nutrition and promote exclusive breastfeeding early breastfeedinginitiation. Early initiation of breastfeeding has many benefits for both mother and baby. This study aimed to comparemeconium spending time and meconium color change and the incidence of physiologic jaundice in infants whoreceived and did not receive early breastfeeding initiation (IMD). This study was a cross sectional analytical studyconducted at the Achmad Mochtar Hospital Bukittinggi. Forty-two maternity patients divided into two groups thatprovide IMD and unprovide IMD group to her baby. In each group assessed first meconium spending time in minutes,the time change meconium original colour of dark green to yellow and counted since birth in hours and the incidenceof physiologic jaundice in infants. All babies kept getting breastfeeding. There were no significant differences in themean time the first meconium spending time in both groups (131.42 minutes and 163.33 minutes, p> 0.05). There aresignificant differences in the mean time meconium colour changes from dark green to yellow (50.14 hours and 94.36hours, p <0.05). Early initiation of breastfeeding also lowers the incidence of physiological jaundice were significantly(p <0.05). Early initiation of breastfeeding did not affect spending time first meconium but accelerate meconiumcolor changes from dark green to yellow. Early initiation of breastfeeding also lowers the incidence of neonataljaundice.